Diagnostic utility of p501s (prostein) in comparison to prostate specific antigen (PSA) for the detection of metastatic prostatic adenocarcinoma - Parwani Anil V; Dhir Rajiv; Yin Ming (BMC, 2007)
Abstract Background Immunohistochemical detection of prostate specific antigen (PSA) is widely used to identify metastatic prostatic adenocarcinoma. However, PSA may not be expressed in some poorly differentiated prostatic carcinomas and its immunoreactivity has been found in some non-prostatic tissues. P501s (prostein) is a prostate-specific marker that is expressed in the cytoplasm of benign and malignant prostatic glandular cells. It has not been detected in any other normal or malignant tissues. The purpose of this study was to evaluate the expression of P501s in metastatic prostatic adenocarcinoma and compare its expression with PSA. Methods Immunohistochemical stains with anti-P501s antibodies were performed on 5-micron sections of tissue microarray (TMA) specimens. The TMA is constructed with normal donor prostates (NDP), prostatic adenocarcinoma (PRCA), non-neoplastic prostatic tissues adjacent to malignant glands (NAT), benign prostatic hyperplasia (BPH), high-grade prostatic neoplasia (PIN), metastatic adenocarcinoma to lymph nodes (MLN), metastatic adenocarcinoma to other sites (MC), and samples of benign testis, colon, adrenal and kidney. The two groups of metastatic lesions were also subjected to stains with antibodies to PSA. A composite score (ranging from 0 to 3) was assigned to score intensity of staining. Results Granular staining pattern of p501s was seen in all benign glands (score = 1.77 - 2.1) and malignant acini (score = 1.52) at the apical aspect of cytoplasm, predominantly adjacent to the nuclei. No staining was observed in controls including testis, colon, adrenal and kidney. The MLN group received a score of 1.0, with 10% of cases negative for p501s. The MC cases had a score of 0.64, with 16.7% of case showing loss of p501s expression. Although the metastatic lesions demonstrated similar rate of negative expression with PSA antibody, only 2 MC cases (3.3%) showed simultaneous negative stains for both P501S and PSA. Conclusion P501s is an organ specific marker for benign and malignant prostatic epithelial cells. Its characteristic cytoplasmic stain pattern provides an additional valuable immunomarker for detection of metastatic prostatic malignancy, even though the intensity of its expression is reduced, as in the case with PSA. Simultaneous stains with P501S and PSA will greatly improve the detection rate and identify a significant majority of the metastases.